The Mutation towards the Creative Democracies - Agusti-Cullell, Jaume (Recent Trends in Arts and Social Studies Vol. 3, 2023)
This chapter provides an overview of Creative Democracies. I focus on the shift from preindustrial authoritarian cultures to societies established on the social embodiment of free creative intelligence, which I refer to as creative democracies. I describe the five fundamental creative energies that comprise human intelligence: interest in reality, semiotic communication, secondary symbiosis, generalised research, and liberation. Creative intelligence and its creations are inseparable; the first creates the second, while only the second shows the first. These thoughts can be seen as the results of my meditation inquiry into the intelligence of humans. In terms of this type of research, I consider myself to be beginner. I believe that the evolution of these democracies is a necessary result of the mutation process that humanity is currently undergoing. It began during the European Renaissance and has now reached a tipping point. Either a healthy collective life within creative democracies or total catastrophe awaits us. I attempt various variations on a few fundamental themes, as in a symphony, taking the chance to extend and deeper into them from a variety of diverse angles.